Theory of Reason Action to Predict Perception of Professionalism and Implementation of Patient Safety among Clinical Nurses: A Path Analysis - Miralda Nasta Indah Anggraini; Rian Adi Pamungkas; Wahyuni D Purwat (Alta Dharma Publisher, 2021)
Background: Patient safety is a fundamental principle of health care and the right of every patient in receiving health services. Patient safety performance as the quality of a hospital organization is affected by the performance of nurses. Objective: This study aimed at investigating the implementation of the theory of reason action model to explain the perception of professionalism and the implementation of patient safety in nurses. Method: The design of this study is a correlational quantitative analytic study with a cross-sectional approach. The analysis technique used is path analysis. The sample of this study was all nurses at Hospital ABC Tangerang, with as many as 105 respondents. Results: This research showed that 1) workload and motivation variables simultaneously affected the implementation of patient safety with the perception of professionalism as an intervening variable (probability level 0.285> 0.05), 2) there was a negative and significant effect of workload on the implementation of patient safety (p-value 0.012 <0.05),3) there was a negative and significant effect of workload on the perception of professional (p-value 0.000 <0.05), 4) motivation variable positively affected the implementation of patient safety (p-value 0.032 <0.05), 5) motivation variable positively affected the perception of professional (p-value 0.000 <0.05) and 6) the perception of professionalism positively affected the implementation of patient safety (p-value 0.000 <0.05). Conclusion: Nurses who have a high motivation to work will behave and act professionally to the duties and responsibilities so that the implementation of patient safety can be achieved. Management should manage the remuneration system of nurses, monitoring, evaluation, and the human resources management system so that the implementation of patient safety remain qualified